Temperature effects on the reproductive performance of Aedes aegypti (Diptera: Culicidae) mosquitoes in Dhaka City, Bangladesh - Sultana, Afroza; Islam, Ashekul; Hasan, Tanvir (Bangladesh Journal of Zoology, 2024)
Abstract not available Bangladesh J. Zool. 51(3): 361-369, 2023